First report of shoot blight of grapevine caused by Sclerotinia sclerotiorum in Illes Balears, Mallorca, Spain - Perelló, Analía E. (2024)
Fil: Perelló, Analía E. Pontificia Universidad Católica Argentina, Facultad de Ingeniería y Ciencias Agrarias. Laboratorio e producción vegetal; Argentina